Downsizing future USAF fighter forces living within the constraints of history - Lewis, Kevin N. (Rand, 1995)
How should U.S. Air Force fighter forces be structured and organized in the future? No one doubts that airpower will play a continuing vital role in future American defense planning. That role may, in fact, grow in importance as U.S. defense downsizing continues, as the global strategic environment evolves, and as technological and other developments present new operational opportunities. Such capabilities are expensive to modernize and operate however, so decisions about fighter force size, mix, and other attributes are fraught with controversy--and further declines in the defense budget could intensify debate over these forces. This report provides a framework for approaching systematically certain issues pertinent to a future fighter force roadmap. It presents alternative postures, based on force and mission planning themes, and it discusses selected issues associated with the operational, modernization, and other implications of those alternatives. While the ultimate USAF fighter force may differ from the options presented here, the methodology offered nevertheless highlights key planning issues and has considerable value for that reason.
Keywords: United States. -- Air Force; Air Force planning; Air Force; Fighter aircraft; Fighter planes -- United States; Military planning -- United States; Militärische Planung; Jagdflugzeug; USA